Leak test for solid oxide fuel cells and solid oxide electrolysis cells - Chou, Yeong-Shyung; Hardy, John; Marina, Olga A. (Frontiers in Energy Research, 2022)
A simple, fast, and economical alcohol penetration method for assessing the solid oxide cell to metal window frame seal in a typical planar design is presented. An alcohol such as ethanol or isopropanol is placed into the cavity of a cell sealed to the window frame. Within 3–5 min, one can determine if the glass seal is hermetic by visual observation along the seal edges on the side of the sealed frame. Cross bubbling and open circuit voltage methods for determining whether the seal failed or cracked at high temperature after final stack firing are also discussed.